PERAN TATA LETAK RUANG KANTOR DALAM MENINGKATKAN EFEKTIVITAS KOMUNIKASI GURU - Lu’luatun Nadiyah; Maslakhah Ulin Nuha; Nur Faizun; Dahlia Dahlia (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2023)
A good work environment is an environment that is able to create a clean and comfortable atmosphere. To create a work environment that needs to be organized. The arrangement of office workspaces in schools is very important. The existence of an office layout affects the effectiveness of carrying out activities in the office, including in creating smooth communication between employees to avoid misunderstandings. This study uses descriptive qualitative research methods through interviews, observation and documentation with the aim of knowing the role of office space layout in increasing the effectiveness of teacher communication at SDN Sidoagung 3. The results of the study show that the layout of the office space plays a role in increasing the effectiveness of teacher communication at SDN Sidoagung 3. Even though it has limited land, SDN Sidoagung 3 tries to create good communication between fellow teachers and the school principal by setting up circular tables and providing empty space in the middle of the room and providing a special room for counseling.